La reine Mélisende - Mutafian, Claude Armen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
When, at the end of the 12th century, the Crusaders captured Jerusalem and founded four Latin states in Syria, they needed women to settle there. However, for both religious and political reasons, the choice was practically limited to Armenian princesses, who thus found themselves at the head of these states. The most important was the Kingdom of Jerusalem, whose first holder, Baldwin I, had taken the Armenian princess Arda as his second wife. She was quickly repudiated and left little trace. His successor, Baldwin II, married Morfia, daughter of the Armenian prince Gabriel of Melitene. The couple had four daughters, the eldest of whom, Melisende, became Queen of Jerusalem by right upon her father’s death in 1131. Virtually ignored by Armenian historiography—probably because of their conversion to Chalcedonianism—these Armenian queens are well known from Greco-Latin and Syriac sources. Melisende remains a mythical figure of the Christian East: brilliant, cultured, tolerant, yet uncompromising in her powers. According to Archbishop William of Tyre, it was she “who had ruled the kingdom for thirty years and more”.